Food Cultures of India - Chaudhuri, Sarit K.,; Nath, Debarshi Prasad,; Sarma, Dhurjjati, (Brill | Manohar Publishers & Distributors, 2024)
In recent times, Food Studies has emerged as an important interdisciplinary field of enquiry, situated at the convergence point of many disciplines. Food Studies is not just about the study of food itself. One could argue that the trajectory of development of Food Studies has been along the similar lines as Cultural Studies (which also, is not only about the study of culture per se). Food Studies deals with more than the mere production, consumption, aesthetic appreciation, and cataloguing of food-related practices. It provides the vantage point to look at the relationship between food and people from the variety of perspectives offered by disciplines, such as arts, science, management, technology, sociology, cultural studies, economics, health, social justice, literature, anthropology, and history. In the context of these exciting developments, the present volume brings together a collection of essays written by academics and scholars belonging to a wide range of disciplines, and who have brought in their subject-expertise towards analysing various dimensions of Food Studies, covering its interface with folklore, social practices, fictional representation, famines, memory, and media studies.